2019
DOI: 10.1186/s13018-019-1127-8
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of knee extension and incidence of extension deficits following anterior cruciate ligament injury and treatment: a systematic review protocol

Abstract: Introduction Knee extension deficit or loss of extension (LOE) is a potential complication following ACL reconstruction (ACLR); however, the change in postoperative knee extension during rehabilitation is not well defined. The aim of this review is to establish the trajectory of knee extension recovery and incidence of knee extension deficit during rehabilitation after ACL rupture. Methods and analysis A systematic search will be conducted in MEDLINE, Embase, Cochrane L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…This review was reported as per the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) statement 13 . A protocol for the systematic review was established a priori 14 and registered on the PROSPERO International Prospective Register of Systematic Reviews, registration number CRD42018092295.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This review was reported as per the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) statement 13 . A protocol for the systematic review was established a priori 14 and registered on the PROSPERO International Prospective Register of Systematic Reviews, registration number CRD42018092295.…”
Section: Methodsmentioning
confidence: 99%
“…An updated search was performed in November 2021. Searches were performed with the terms in the protoco 14 in post-review databases (Pubmed, Cochrane Trials Database and The Lens (lens.org)). The Lens is an open-access platform archiving hundreds of millions of scholarly articles.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations